Short Communication: Polymorphism at third exon of the Myostatin gene and its association with growth and carcass traits in Batur sheep - Hassan Ishag Hassan Haren; Dattadewi Purwantini; Mas Yedi Sumaryadi; Prayitno Prayitno (Society for Indonesian Biodiversity, 2020)
Abstract. Haren HIH, Purwantini D, Sumaryadi MY, Prayitno. 2020. Short Communication: Polymorphism at third exon of the Myostatin gene and its association with growth and carcass traits in Batur sheep. Biodiversitas 21: 2074-2078. The present study aimed to investigate the association between myostatin (MSTN) genotype and two traits, growth and carcass, in Batur sheep. Blood samples representing thirty head were collected and genomic DNA was extracted. A specific primer designed to amplify the MSTN gene, samples sequenced then, used the BioEdit program to identify any mutation. Calculation of genotypes, gene and allele frequencies, heterozygosities, and Chi-square test was performed. Only two alleles observed (G and C) resulted in three genotypes. 11 polymorphic sites were observed, transversion at c.*121G>C, and one individual G>A which disrupted reading frame of whole MSTN sequenced, genotypic and allelic frequencies were 0.552 GG, 0.379 GC, and 0.069 CC, where the allele frequency was 0.741 G and 0.259 C. Lambs that carrying genotype GC had slightly more pre-slaughter weight, hot carcass weight, cold carcass weight, carcass length, and total yield (lion, shoulder, leg yield, and thigh) compared to those carrying genotype GG. There was no significant effect of the MSTN genotype on carcass traits (p=0.05). Polymorphic site c.*121 G>C is present in Batur sheep for the first time about the association with the MSTN gene however, it has not effects weaning weight, 6-month weight, and studied carcass traits.